Development Of QR Code-Based Data Sharing Web Application Using System Development Life Cycle Method - Surya Tjahyadi (Journal of Information System and Technology (JOINT), 2021)
The purpose of this thesis is to study the capabilities and limitations of QR codes as a data sharing media. For this study, author has developed a web application to provide QR code management for users. The web application is implemented in a website named Quick Save which provides data storage, sharing, and QR code generator service. With this website, author can analyze problems and methods of sharing encrypted data in a quick and effective way. The encrypted data is written into the QR code which serves as a link between users and the data or file stored in the web application storage. The method that is used in this thesis study is the System Development Life Cycle method. Based the on the result of the thesis study, author concludes that the implementation of data sharing web application can provide encrypted data sharing, file storing and downloading service for user by using a QR code scanner from their mobile device. The web application has also fulfilled author’s need in researching the capabilities of QR code.